Imagining gay paradise : Bali, Bangkok, and cyber-Singapore - Atkins, Gary, 1949- (Hong Kong University Press ; Eurospan [distributor], 2012)
Mages of Manhood asks the question: How have gay/queer men in Southeast Asia used images of paradise to construct homes for themselves and for the different ideas of manhood they represent? The book examines how three gay men in Bali, Bangkok, and Singapore have deployed different ideas of "paradise" over the past century to create a sense of refuge and to dissent from typical notions of manhood and masculinity. For the disciplines of queer studies, gender studies, communication, and Southeast Asian studies, it provides (1) a "queer reading" of Walter Spies, a gay German painter who in the 1930s helped turned Bali into an island imagined as an ideal male aesthetic state; (2) a historical account of the absorption of Western notions of romantic heterosexual monogamy in Thailand during the reign of King Rama VI, providing an analysis of his plays, and the subsequent resistance to those notions expressed through an erotic, architectural paradise called Babylon created by a post-World War II Thai named Khun Toc; and (3) an account and analysis of the "cyber-paradise" created by a young Singaporean named Stuart Koe. The book examines their pursuit of sexual justice, the ideologies of manhood they challenged, the different types of gay spaces they created (geographic, architectural, online), and the political obstacles they have encountered. Because of its historical sweep and its focus on the relationship between gay men and ideas of Edenic space, it makes an important contribution to understanding gay/queer life in Southeast Asia